A systematic review on the role of reclaimed asphalt pavement materials: Insights into performance and sustainability - Mayank Sukhija; Erdem Coleri (Cleaner Materials)
Recycling practices have become stringent, essentially to overcome scarcity and higher cost of natural resources such as asphalt binder and mineral aggregates. The desire to conserve these natural resources and achieve sustainability in road construction has paved the way for the application of reclaimed asphalt pavement (RAP) material for paving purposes. This state-of-the-art review intends to provide a comprehensive overview of RAP-inclusive asphalt binders and mixtures based on laboratory and field investigations. The review covers various aspects of RAP utilization, starting with a detailed methodology for characterizing RAP material. This includes the extraction and recovery process, the effectiveness of solvents, and associated risk factors. Understanding these processes is crucial for assessing the suitability of RAP in asphalt mixtures. As per the review, the most commonly used extraction and recovery methods are centrifuge extraction and rotavapor with trichloroethylene and n-propyl bromide solvents. Emphases were given on the extent of change in chemical and morphological properties of asphalt binder with the application of RAP material. In addition, this review addresses the impact of using RAP material on the cost and environmental burdens. Based on the literatures, with the use of RAP, the reduction in cost can range from 5% to 68%, along with 3%-95% lower impact on the environment relative to the no RAP condition. As a whole, the compiled literature underscores the feasibility of using RAP as a major step towards constructing new asphalt pavements with adequate mechanical performance while promoting economic and environmental stewardship.